The effect of sewage effluent from De Beers marine diamond mining operations on the expression of cytochrome P450 (CYP1A) and vitellogenin (vtg),Cytochrome P450 monooxygenase 1A (CYP1A) and vitellogenin (vtg) in Cape hake and the effect of sewage effluent from De Beers Marine Namibia Diamond mining operations on the expression of CYP1A - De Almeida, Louise (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology)
Sewage effluents disposed into the marine environment from De Beers Marine Namibia diamond mining vessels have the potential to cause endocrine disruptive effects in marine organisms. Endocrine disruption refers to the alteration of the normal functioning of the endocrine system and various chemicals have the ability to mimic hormones, effecting endogenous hormone synthesis, transport, receptor interaction and intracellular signaling. The potential endocrine disruptive effects, caused by the release of different types of sewage effluents into the ocean, on fish species is a concern due to the commercial importance of fish species found in the mining area e.g. hake, sole, horse mackerel. Increased awareness of marine environmental degradation due to the presence of chemical contaminants has resulted in research being done on early warning systems, in the form of biomarkers. Cytochrome P450 monooxygenase 1A (CYP1A) and vitellogenin (vtg) are important proteins found in fish liver and blood, that have been used as biomarkers for the detection of pollutants in fish. CYP1A is a subfamily of the P450 superfamily of enzymes and catalyzes the oxidation, hydrolysis and reduction of exogenous and endogenous compounds (phase I reactions) and thus has the capacity to regulate the metabolism of several organic contaminants. CYP1A expression is altered by exposure to planar xenobiotic compounds e.g. polyaromatic hydrocarbons. Vtg is an important precursor for egg yolk proteins and plays a role in the growth and development of an oocyte. Expression of this protein is altered upon exposure to estrogenic compounds. The aim of this project was to isolate CYP1A from fish liver by differential centrifugation and optimize conditions for the CYP1A-mediated ethoxyresorufin-Odeethylase (EROD) assay and western blot analysis (to assess CYP1A expression). Another aim of this study was to evaluate the potential effects of biologically disruptive chemicals from sewage effluents, discharged into the marine environment, on the expression of CYP1A in two species of hake, Merluccius capensis and M. paradoxus (Cape hake). CYP1A in Cape hake is approximately a 60 kDa protein and the highest EROD activity was detected in the microsomal fraction after differential centrifugation. Optimal EROD assay conditions were observed at pH 7.5, a temperature of 25 °C, 10 μl of sample and a reaction time of 30 seconds. Enzyme stability assays indicated a drastic decrease in enzyme activity after 30 seconds. The EROD assay was not NADPH dependent but was limited by NADPH supply, with an increase of 300% in EROD activity being observed with the addition of 0.1 M exogenous NADPH. The addition of dicumarol (40 μM), a phase II enzyme inhibitor, showed a 232% increase in EROD activity. This is because dicumarol inhibited enzymes with the capacity to metabolize the product (resorufin) of the EROD reaction. With regard to western blot analysis, the optimal primary (rabbit antifish CYP1A peptide) and secondary (anti-mouse/rabbit antibody-horseradish peroxidase conjugate (POD)) antibody dilutions were determined to be 1:1000 and 1:5000, respectively. The comparison of CYP1A expression in Cape hake samples from De Beers Marine mining area and reference sites showed higher EROD activity (16.29 ± 0.91 pmol/min) in fish samples from the mining area in comparison to the reference site (10.42 ± 2.65 pmol/min). Western blot analysis was in agreement with the EROD assay results and a higher CYP1A expression was observed in fish from the mining sites. The increased CYP1A expression observed in fish from the mining area is not definitively an indication of a pollutant effect in the environment, as several environmental and biological factors (e.g. photoperiod and age) must also be considered before reaching this conclusion. Another aim of this study was to purify vtg from Cape hake blood samples. Cape hake vtg was purified from fish plasma by selective precipitation with MgCl2 and EDTA. Precipitated sample was subjected to anion exchange chromatography using fast protein liquid chromatography (FPLC). Vtg eluted as two broad peaks and had a molecular weight above 200 kDa. SDS-PAGE analysis also resolved smaller molecular weight proteins below 70 kDa, which were thought to be vitellogenin cleavage proteins, lipovitellin and phosphovitins. Western blot analysis was performed; however, it did not produce any conclusive results. The purification of vtg enables further studies in characterizing this protein and developing assay aimed at detecting estrogenic pollutants in the marine environment
Keywords: De Beers Consolidated Mines; Sewage disposal in rivers, lakes, etc. -- Namibia; Endocrine disrupting chemicals in water -- Namibia; Merluccius capensis -- Namibia; Merluccius -- Namibia; Water -- Pollution -- Namibia